Les tâches appropriées des professeurs d’enseignement professionnel - Hélène Veyrac; Nina Asloum (Activités)
Teachers of vocational disciplines are faced with particular constraints related to the fact that they teach occupational skills. These skills are described in official reference manuals, which necessarily narrows the field of the practical activity they are intended to cover. This reduction is one of the causes of the gap that separates vocational training and actual professional practice.To what extent are teachers aware of this gap? What do they do in order to fill it? Answers can be found through the description of “appropriate tasks”. Research interviews, lesson observations and self-confrontations with teachers in the domain of landscape planning lead to a better understanding of the work done by teachers in vocational training.The data we have collected illustrates teachers’ different appropriate tasks: accepting the gap and informing the pupils about it, innovative teaching practices, showing the contradictions between reference manuals and effective professional practice. In summary, this paper illustrates how the gap between vocational training and professional practice is filled by the teachers, and contributes to the development of research on the analysis of work by teachers.